Entrepreneurship vs. standard of living of the population in western Poland: a spatial analysis - Malinowski, Mariusz (Przedsiębiorczość a poziom życia mieszkańców w Polsce Zachodniej – analiza przestrzenna, 2020)
The author of this paper intends to present the relationships between the level of entrepreneurship and the population’s standard of living. This study covered 112 districts in the Dolnośląskie, Lubuskie, Opolskie, Wielkopolskie and Zachodniopomorskie voivodeships. Entrepreneurship levels and standard of living were assessed with the use of TOPSIS. The variables were selected based on relevance, statistical and formal criteria (mainly including completeness and availability of 2018 data for the objects covered by the study). As shown by this study, moderate correlation exists between the phenomena considered. The results of spatial regression analysis provide grounds for concluding that a 1% increase in the synthetic indicator of entrepreneurship results, ceteris paribus, in a 0.31% increase in the synthetic indicator of standard of living at district level
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 127-145
Keywords: standard of living; linear ordering; spatial regression; poziom życia; porządkowanie liniowe; regresja przestrzenna